Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1007/s13399-022-03264-9
|View full text |Cite
|
Sign up to set email alerts
|

Biogas production from the landfilled easily degradable fraction of municipal solid waste: mining strategy for energy recovery

Abstract: The growing demand for space and financial resources to manage current and new municipal solid waste (MSW) landfills has become a massive challenge for several countries. Additionally, landfills contribute to adverse environmental impacts such as pollution and CO 2 (carbon dioxide) and CH 4 (methane) emissions. This paper has analyzed the possibility of producing biogas from landfilled MSW. An easily degradable fraction of landfilled MSW with 8 years of landfilling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…With the data obtained from the Table 6, the generation of tons of greenhouse gases (CO2, CH4 and N2O) is calculated from the year 2000 and up to 2031 (Table 7) The generation of GHG were plotted according to the results obtained at Table 7 (Figure 5) for the years 2000 to 2031, although the generation continues for more than 50 years, due to persistent degradation of de organic fraction of waste [26]. However, the Mexican Biogas Model does not establish a change in the composition of biogas, which does occur given that previous studies have shown that methane can represent up to 65 % of emissions and that over time this fraction will diminishing to almost disappearing [27].…”
Section: Resultsmentioning
confidence: 99%
“…With the data obtained from the Table 6, the generation of tons of greenhouse gases (CO2, CH4 and N2O) is calculated from the year 2000 and up to 2031 (Table 7) The generation of GHG were plotted according to the results obtained at Table 7 (Figure 5) for the years 2000 to 2031, although the generation continues for more than 50 years, due to persistent degradation of de organic fraction of waste [26]. However, the Mexican Biogas Model does not establish a change in the composition of biogas, which does occur given that previous studies have shown that methane can represent up to 65 % of emissions and that over time this fraction will diminishing to almost disappearing [27].…”
Section: Resultsmentioning
confidence: 99%